Chavelling - Ong, Xin Hong (2019)
In a technological era, we often immerse in a world behind a screen, a convenient means of travel. However most of our senses remain untouched. Throughout my journeys, tea is a souvenir I often share and receive from people. In Chavelling, tea is neither just a thirst quenching beverage nor a drink to stay awake. Tea plays an important role in rejuvenation. With four traditional Chinese tea as the highlight of this project, Chavelling is represented by a series of light sculptures that aim to cultivate empathic curiosity within tea drinkers seeking rejuvenation by bridging screen-based and real experiences. Chavelling embarks on China, where tea drinking culture originates. Making reference to two different Chinese inventions of paper and tea, the sculptures were meticulously made through paper moulding technique with handmade paper and glue. “Tea paper” in this project refers to paper made from a blend of recycled office paper and waste tea leaves. The abstract form for each sculpture was inspired by the variation of tea processing techniques and the inherent quality of tea influenced by the people and the climate of different regions in China. Together with its larger than life appearance, tea fragrance oil introduced to the porous surface of illuminating paper sculptures expand our senses, compelling us to look more closely at tea leaves. Through stimulation of visual, tactile and olfactory senses, Chavelling encourages exploration of tea origins. Designed to be displayed in tea establishments, Chavelling serves to promote tea’s origin, culture and sustainability.